1998
DOI: 10.1159/000044941
|View full text |Cite
|
Sign up to set email alerts
|

Anti-CD8 Monoclonal Antibody Protects against Spontaneous IgA Nephropathy in ddY Mice

Abstract: We investigated the effects of anti-CD4 monoclonal antibody (mAb) and/or anti-CD8 mAb in ddY mice, an animal model of spontaneous IgA nephropathy. Female ddY mice were treated with 18 intravenous injections of anti-CD4 and/or anti-CD8 mAb at 2-week intervals. This was based on our observation that a single injection of anti-CD4 mAb or anti-CD8 mAb caused a selective depletion in CD4+ T cells for 2 weeks and CD8+ T cells for 4 weeks, respectively. The level of proteinuria, serum IgA, and changes in the histopat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…In addition, Tomino et al uncovered that CD8 + T cells were the most abundant glomerular-infiltrating cell in IgAN patients [ 74 ]. Anti-CD8 T cell treatment has been proved to trigger a profitable effect of suppressing mesangial expansion in an animal model of IgAN [ 75 ]. Another study showed that, compared to children with non-progressive IgAN, significantly higher percentages of CD8 + T cells in the glomeruli and in the interstitium were detected in the children with progressive IgAN [ 76 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Tomino et al uncovered that CD8 + T cells were the most abundant glomerular-infiltrating cell in IgAN patients [ 74 ]. Anti-CD8 T cell treatment has been proved to trigger a profitable effect of suppressing mesangial expansion in an animal model of IgAN [ 75 ]. Another study showed that, compared to children with non-progressive IgAN, significantly higher percentages of CD8 + T cells in the glomeruli and in the interstitium were detected in the children with progressive IgAN [ 76 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, some experimental studies have indicated that CD8 + cells and the soluble factor secreted by them might directly and/or indirectly promote tissue damage [16]. Recently, Shimamine et al [17] reported that anti-CD8 T-lymphocyte treatment produced a protective effect against mesangial injury in ddY mice, an animal model of spontaneous IgAN.…”
Section: Discussionmentioning
confidence: 99%
“…Sabadini et al (88) reported that the degree of interstitial CD8 + lymphocyte infiltration was correlated with the severity of interstitial fibrosis and renal impairment. Shimamine et al (89) reported that anti-CD8 T-lymphocyte treatment produced a protective effect against mesangial injury in ddY mice, an animal model of spontaneous IgAN. In another study, 20 children with IgAN who were followed for >5 years were divided into the progressive (n=5) and non-progressive groups (n=15).…”
Section: Cd8 + Cellsmentioning
confidence: 99%